Method for producing adhesive film and adhesive film, and method for producing structural body and structural body
By forming a curing agent-free adhesive film and transferring a latent curing agent onto the film surface, the method addresses storage stability and adhesive strength issues, facilitating flexible production and effective low-temperature curing for smaller electronic components.
Patent Information
- Application Number
- JP2023095916
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-09
- Publication Date
- 2024-12-19
AI Technical Summary
Existing adhesive films using latent curing agents face challenges with storage stability due to curing reactions during film formation and restrictions on solvent use, which are exacerbated by the need for low-temperature curing to prevent heat damage in smaller and thinner electronic components.
A method involving a curing agent-free adhesive composition is formed into a film layer, followed by transferring a latent curing agent onto the film surface or embedding it within the film layer, allowing for controlled exposure and reaction initiation, thereby suppressing curing reactions during film production and enhancing storage stability.
This approach improves storage stability and adhesive strength by preventing premature curing reactions, enabling flexible production schedules and allowing for the use of latent curing agents that were previously difficult to utilize due to solvent resistance and temperature constraints.
Smart Images

Figure 2024176983000001_ABST
Abstract
Description
[Technical field]
[0001] The present technology relates to a manufacturing method of an adhesive film containing a curing agent, an adhesive film, a manufacturing method of a structure, and a structure. [Background technology]
[0002] For example, in the mounting of electronic components, an adhesive film is sandwiched between opposing electronic components and hardened by heating and pressing with a tool. As components become smaller and thinner, damage caused by heat becomes more difficult to avoid, so there is a strong demand for lower mounting temperatures.
[0003] In addition, latent curing agents that become reactive only when exposed to external stimuli such as heat or light are used as curing agents in adhesive films. For example, Patent Document 1 describes a technology that makes it possible to use a one-component adhesive that is used by mixing two components by encapsulating a curing agent that can be used in low-temperature reactions and making it latent.
[0004] However, when a latent curing agent is used, there are restrictions on the amount and type of solvent used during film production, and there are also restrictions on the composition. In addition, when low-temperature reactivity is required, the curing reaction proceeds due to the heat of drying during film formation, resulting in reduced storage stability. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2016-056274 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present technology is intended to solve the above-mentioned problems, and provides a method for producing an adhesive film having excellent storage stability, an adhesive film, a method for producing a structure, and a structure. [Means for solving the problem]
[0007] As a result of intensive investigations into the above problems, the present inventors have found that the above problems can be solved by the following technology, and have completed the present technology. [1] forming a film layer of a non-curing agent-containing adhesive composition that does not contain a curing agent; a disposing step of transferring the latent curing agent from a transfer substrate on which the latent curing agent is disposed to the film layer, and disposing the latent curing agent so as to be exposed from at least one surface of the film layer or to be adjacent to at least one surface of the film layer; A method for producing an adhesive film having the above structure. [2] The method for producing an adhesive film according to claim [1], wherein the latent curing agent is disposed in the film layer in a lump form. [3] The method for producing an adhesive film according to [1] or [2], wherein the latent curing agent is in a microencapsulated form. [4] the curing agent-free adhesive composition comprises a film-forming resin, a cationically polymerizable compound, and a silane-based compound; The method for producing an adhesive film according to [1] or [2], wherein the latent curing agent is an aluminum chelate-based latent curing agent. [5] The method for producing an adhesive film according to [1] or [2], further comprising a conductive particle arranging step of arranging conductive particles in the film layer. [6] The method for producing an adhesive film according to [1] or [2], in the molding step, conductive particles are blended with the curing agent-free adhesive composition to mold a film layer containing the conductive particles. [7] A film layer of an adhesive composition having a latent curing agent exposed from at least one surface or disposed adjacent to at least one surface, The average particle size of the latent curing agent is 2 μm or more and 50 μm or less, The thickness of the film layer is from 3 μm to 40 μm. [8] a latent curing agent is exposed from at least one surface or disposed adjacent to at least one surface, the film layer containing conductive particles; The average particle size of the latent curing agent is 2 μm or more and 50 μm or less, The conductive film, wherein the thickness of the film layer is 3 μm or more and 40 μm or less. [9] a latent curing agent is exposed from at least one surface or disposed adjacent to at least one surface, the film layer containing conductive particles; The average particle size of the latent curing agent is 2 μm or more and 50 μm or less, The thickness of the film layer is 3 μm or more and 40 μm or less.
[10] A method for manufacturing a structure in which a first part and a second part are bonded together via the adhesive film described in [7] above.
[11] A method for manufacturing a connection structure that connects a terminal of a first component and a terminal of a second component via the adhesive film described in [7] above, the conductive film described in [8] above, or the anisotropic conductive film described in [9] above.
[12] A structure in which a first part and a second part are bonded via the adhesive film described in [7] above.
[13] A connection structure in which a terminal of a first electronic component and a terminal of a second electronic component are connected via the adhesive film described in [7] above, the conductive film described in [8] above, or the anisotropic conductive film described in [9] above. Effect of the Invention
[0008] According to this technology, by disposing the latent curing agent after film formation, the progress of the curing reaction caused by the solvent of the latent curing agent can be suppressed, and excellent storage stability can be obtained. In addition, by disposing the latent curing agent on the surface of the film layer, the reaction caused by the curing agent is initiated, and excellent adhesive strength can be obtained. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a flow chart showing the process from production to use of the adhesive film according to the present embodiment. [Diagram 2] FIG. 2 is a cross-sectional view that typically shows a state in which a transfer substrate filled with a latent curing agent and a film layer are placed opposite each other. [Diagram 3] FIG. 3 is a cross-sectional view that typically shows a state in which a latent curing agent is attached to the surface of a film layer. [Figure 4] FIG. 4 is a cross-sectional view that illustrates a state in which a latent curing agent is pressed into a film layer. [Diagram 5] FIG. 5 is a cross-sectional view that illustrates a schematic diagram of an adhesive film of the first embodiment. [Figure 6] FIG. 6 is a cross-sectional view that illustrates a modified example of the adhesive film of the first embodiment. [Figure 7] FIG. 7 is a cross-sectional view that illustrates a schematic diagram of an adhesive film according to the second embodiment. [Figure 8] FIG. 8 is a cross-sectional view that illustrates a schematic diagram of an adhesive film according to a third embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, embodiments of the present technology will be described in detail with reference to the drawings in the following order. 1. Manufacturing method of adhesive film 2. Adhesive film 3. Manufacturing method of structure and structure 4. Working Example
[0011] <1. Manufacturing method of adhesive film> The method for producing an adhesive film according to the present embodiment includes a forming step of forming a film layer of a curing agent-free adhesive composition that does not contain a curing agent, and a disposing step of transferring a latent curing agent from a transfer substrate on which the latent curing agent is disposed to the film layer, and exposing the latent curing agent from at least one surface of the film layer or disposing the latent curing agent in close proximity to at least one surface of the film layer. This makes it possible to suppress the progress of a curing reaction caused by a solvent of the latent curing agent, and to obtain excellent storage stability.
[0012] Here, the curing agent-free adhesive composition refers to one that does not contain a curing agent and does not function as an adhesive when subjected to external stimuli such as heat or light. A latent curing agent refers to a powder solid particle that becomes reactive only when subjected to external stimuli such as heat or light. Examples of latent curing agents include a microcapsule type in which the curing agent component is used as a core and is covered with a coating agent (shell) such as an organic polymer or an inorganic compound, and an impregnation type in which the curing agent component is encapsulated in porous particles.
[0013] FIG. 1 is a flow chart showing the manufacturing to use of the adhesive film according to the present embodiment. As shown in FIG. 1, the manufacturing to use of the adhesive film includes a blending step S1 of blending a curing agent-free adhesive composition, a coating and drying step S2 of applying and drying the curing agent-free adhesive composition to obtain a film, a curing agent pushing step S3 of pushing a curing agent into the surface of the film, a slitting step S4 of obtaining a film of a predetermined width, a reeling step S5 of winding a film of a predetermined width, a pressure bonding step S6 of pulling out the film from the reel and pressure bonding a first electronic component and a second electronic component through the film, and a structure step S7 of obtaining a structure including the first electronic component and the second electronic component. In addition, when manufacturing an anisotropic conductive film in which conductive particles are arranged as an example of an adhesive film, it is preferable to provide the conductive particle arrangement step before or after the curing agent pushing step S3. In addition, the conductive particles may be mixed in advance in the blending step S1, and in this case, the conductive particles are three-dimensionally randomly dispersed in the adhesive film.
[0014] In the conventional method, the production of the adhesive film is started by counting backwards from the mixing time when the hardener is added to the pressing process in anticipation of the reaction of the hardener, so the production line must be operated continuously until the film is wound around the reel and shipped, which places restrictions on production management. In addition, even after shipping, the wound body is stored and managed under the constraints of the manufacturing management of the structure until the adhesive film is used up (the connection process is completed).
[0015] On the other hand, in this embodiment, since the hardener is not added in the blending step S1, the constraints on the amount and type of solvent can be reduced. In addition, in the coating and drying step S2, the curing reaction can be prevented from progressing due to the heat of drying during film formation. In addition, the hardener pushing step S3 is the start of the reaction of the hardener, and since the manufacturing process (mass production line) can be temporarily stopped before the hardener pushing step S3, the life of the product can be easily controlled when calculated backwards from the pressure bonding step S6. In addition, since the manufacturing schedule and time management become flexible, there is an industrial advantage that the constraints on manufacturing management are significantly reduced compared to the conventional method. In addition, in this embodiment, the adhesive film may be a wound body wound on a reel, and the length of the adhesive film is preferably, for example, 5 m or more because it can be connected using an apparatus, and is preferably 5000 m or less in terms of attachment to the apparatus. In addition, the width of the adhesive film is preferably, for example, 0.5 mm or more and 60 cm or less. The adhesive film may be a sheet, and there is no particular restriction on the size, but for example, one side is preferably 5 cm or more, and more preferably 20 cm or more in terms of use. In the case of a sheet, the maximum length of one side is, for example, 200 cm or less in terms of handling.
[0016] Hereinafter, the molding step (A) of molding the film layer and the disposing step (B) of disposing the latent curing agent will be described with reference to Fig. 2 to Fig. 4. Fig. 2 is a cross-sectional view showing a state in which a transfer substrate filled with a latent curing agent and a film layer are opposed to each other, Fig. 3 is a cross-sectional view showing a state in which a latent curing agent is attached to the surface of the film layer, and Fig. 4 is a cross-sectional view showing a state in which the latent curing agent is pressed into the film layer.
[0017] [Molding process (A)] In the molding step (A), first, a curing agent-free adhesive composition that does not contain a curing agent is prepared. A known insulating binder can be used for the adhesive composition. Examples of the curing type include a heat curing type, a light curing type, and a light-heat combined curing type. For example, a thermal cationic polymerization type resin composition containing an epoxy compound and a thermal cationic polymerization initiator, a thermal anionic polymerization type resin composition containing an epoxy compound and a thermal anionic polymerization initiator, a photoradical polymerization type resin composition containing a (meth)acrylate compound and a photoradical polymerization initiator, and a thermal radical polymerization type resin composition containing a (meth)acrylate compound and a thermal radical polymerization initiator can be mentioned. That is, in the case of a thermal cationic polymerization type resin composition, the curing agent-free adhesive composition does not contain a thermal cationic polymerization initiator, but contains a cationic polymerizable compound such as an epoxy compound.
[0018] A solvent can be used to prepare the curing agent-free adhesive composition, such as propylene glycol monomethyl ether acetate (PMA) or methyl ethyl ketone (MEK).
[0019] Next, the curing agent-free adhesive composition is applied onto a substrate film 11, and dried to evaporate the solvent, forming a film layer 12 of the curing agent-free adhesive composition of a predetermined thickness on the substrate film. The remaining amount of the solvent in the film layer 12 is preferably less than 1%, more preferably less than 0.5%, and even more preferably less than 0.1%. This makes it possible to suppress the progress of the curing reaction caused by the solvent of the latent curing agent, and to obtain excellent storage stability. For example, a PET film that has been subjected to a release treatment with a silicone resin can be suitably used as the substrate film 11.
[0020] [Placement process (B)] In the disposing step (B), first, the latent curing agent 13 is held on the first surface 12A of the film layer 12. Examples of methods for holding the latent curing agent 13 include a transfer method in which the latent curing agent 13 is transferred to the film layer 12 using a transfer substrate 20, and a spraying method in which the latent curing agent 13 is sprayed on the film layer 12. Among these, the transfer method can uniformly dispose the latent curing agent in a plan view, and can also uniformly dispose the latent curing agent in the thickness direction by pressing it with a flat plate or the like after transfer, thereby obtaining excellent adhesive strength (die shear strength, peel strength).
[0021] As shown in FIG. 2, in the transfer method, a transfer substrate 20 filled with a latent curing agent 13 is placed opposite a film layer 12, and the film layer 12 is pressed against the transfer substrate 20, so that the latent curing agent 13 is held on a first surface 12A of the film layer 12.
[0022] The transfer substrate 20 has recesses of a predetermined density formed in a predetermined arrangement. Such a transfer substrate 20 can be produced, for example, by producing a mold having protrusions of a predetermined density in a predetermined arrangement, pouring resin pellets in a molten state into the mold, and cooling and solidifying the mold. The transfer substrate 20 may be, for example, an inorganic material such as silicon, ceramics, glass, or metal such as stainless steel, or an organic material such as various resins, in which openings are formed by a known opening forming method such as a photolithography method. The transfer substrate 20 may be in the form of a plate or a roll.
[0023] 3 and 4, the latent curing agent 13 attached to the first surface 12A of the film layer 12 is pressed into the film layer 12. This allows the latent curing agent 13 to be exposed from the first surface 12A of the film layer 12 or to be disposed close to the first surface 12A of the film layer 12 and dispersed in a plan view. The amount of the latent curing agent 13 embedded in the film layer 12 can be adjusted by the pressing force, temperature, etc. when the latent curing agent 13 is pressed into the film layer 12.
[0024] Alternatively, a plurality of latent curing agents 13 may be filled in one recess of the transfer substrate 20, and the latent curing agents 13 may be arranged in the film layer 12 in the form of lumps. This allows the latent curing agents 13 to be aligned in the film layer 12 even if the particle size of the latent curing agents 13 varies greatly.
[0025] In addition, the number density of the latent curing agent 13 arranged on the film layer 12 is preferably equal to the number density of the recesses of the transfer substrate 20, and may be equal to or less than the number density of the recesses of the transfer substrate 20 when the transfer rate of the latent curing agent 13 is low. When the latent curing agent 13 is arranged on the film layer 12 in the form of clumps, the number density of the latent curing agent 13 may be counted as one clump. That is, the number density may be the number density of the clumps of the latent curing agent 13. The number density of the latent curing agent 13 can be measured by observation with a microscope. The number density of the latent curing agent 13 can be determined based on the content of the latent curing agent 13 in the adhesive composition containing the latent curing agent 13, the area of the film layer 12, the transfer rate of the latent curing agent 13, and the like.
[0026] Also, in the case where the latent curing agent 13 is disposed on the second surface of the film layer 12, the latent curing agent 13 is held on the second surface of the film layer 12 and pressed into the film layer 12 in the same manner as described above. This allows the latent curing agent 13 to be disposed on both surfaces of the film layer 12.
[0027] The method for producing an adhesive film may further include a conductive particle arranging step of arranging conductive particles in the film layer 12. In the conductive particle arranging step, similar to the arranging step (B) of arranging the latent curing agent 13, the conductive particles can be held by a transfer method of transferring the conductive particles to the film layer 12 using a transfer substrate, a scattering method of scattering the conductive particles on the film layer 12, or the like, and the conductive particles can be pushed into the film layer 12 to arrange the conductive particles in the film layer 12. In addition, in the molding step (A), the conductive particles may be blended into a curing agent-free adhesive composition and the conductive particles may be dispersed in the film layer 12. This makes it possible to produce a conductive film or anisotropic conductive film containing conductive particles.
[0028] The arrangement and embedding state of the latent hardener and conductive particles in the film layer and the shape of the resin may conform to those described in Japanese Patent No. 6187665.
[0029] Furthermore, the adhesive film, conductive film, or anisotropic conductive film on which the latent curing agent 13 is disposed may be a laminate of the film layer 12. This can improve, for example, the adhesive strength (die shear strength, peel strength) or the particle capture property of the conductive particles.
[0030] According to such a method for manufacturing an adhesive film, by disposing a latent curing agent on the applied film, it is possible to use a curing agent that has been difficult to use in terms of the temperature and solvent resistance during film formation. In addition, for example, when the latent curing agent is an aluminum chelate-based latent curing agent and conductive particles are disposed, it is possible to manufacture an anisotropic conductive film that can be cured at a low temperature while maintaining the latency without impairing the latency of the curing agent and can provide good adhesion. In addition, when this anisotropic conductive film in which the latent curing agent and conductive particles are disposed is used for an anisotropic conductive connection between electronic components, it is possible to provide a connection with a stable particle arrangement by curing at a low temperature and providing good adhesion.
[0031] In addition, in this manufacturing method, the latent curing agent is not mixed into the liquid adhesive composition, but after the adhesive composition is formed into a film, the latent curing agent is arranged and present near the surface of the film layer. The difference between the adhesive film produced by this manufacturing method and the adhesive film formed by applying a resin composition (liquid, paste, slurry, etc.) containing a latent curing agent can be classified by whether or not the latent curing agent is arranged. The fact that the latent curing agent can be arranged at a predetermined position increases the convenience of the adhesive film, and the performance can be controlled more precisely, and there is no restriction on the composition of the adhesive composition. One example of convenience is that it is possible to make the manufacturing schedule of the adhesive film mentioned above convenient, and one example of more precise control of the performance is that it is possible to arrange the latent curing agent only at a predetermined position on the plane of the adhesive film, and by giving the latent curing agent a planar density distribution, the curing reaction can be changed within the plane of the adhesive film (such as creating a place where the curing proceeds quickly and a place where it does not).
[0032] <2. Adhesive film> The adhesive film according to the present embodiment has a film layer of an adhesive composition in which a latent curing agent is exposed from at least one surface or disposed adjacent to at least one surface. By disposing the latent curing agent on the surface of the foam layer, a curing reaction is initiated, and excellent adhesive strength (die shear strength, peel strength) can be obtained.
[0033] As described above, the adhesive composition may use a known insulating binder. Examples of the curing type include a heat curing type, a light curing type, and a light and heat combined curing type, and examples of the curing type include a thermal cationic polymerization type resin composition containing an epoxy compound and a thermal cationic polymerization initiator, a thermal anionic polymerization type resin composition containing an epoxy compound and a thermal anionic polymerization initiator, a photoradical polymerization type resin composition containing a (meth)acrylate compound and a photoradical polymerization initiator, and a thermal radical polymerization type resin composition containing a (meth)acrylate compound and a thermal radical polymerization initiator.
[0034] Examples of latent curing agents include aluminum chelate-based curing agents, imidazole-based curing agents, hydrazide-based curing agents, boron trifluoride-amine complexes, sulfonium salts, amine imides, polyamine salts, and dicyandiamide. These latent curing agents can be used alone or in combination of two or more, and may be used with a decomposition accelerator, inhibitor, or the like. Among these, by using the above-mentioned adhesive film manufacturing method, it is possible to use an aluminum chelate-based latent curing agent, which has been difficult to use in terms of solvent resistance. By adding an aluminum chelate-based latent curing agent to a cationic polymerizable compound and a silane-based compound, a low-temperature fast-curing thermal cationic polymerization type resin composition can be provided.
[0035] In the following, as an example of an adhesive composition for forming a film layer, a thermal cationic polymerization type resin composition containing a film-forming resin, a cationic polymerizable compound, an aluminum chelate-based latent curing agent, and a silane-based compound will be described.
[0036] (film-forming resin) The film-forming resin corresponds to a high molecular weight resin having an average molecular weight of, for example, 10,000 or more, and from the viewpoint of film formability, the average molecular weight is preferably about 10,000 to 80,000. Examples of the film-forming resin include various resins such as phenoxy resin, epoxy resin, polyester resin, polyurethane resin, polyester urethane resin, acrylic resin, polyimide resin, butyral resin, etc., which may be used alone or in combination of two or more kinds. Among these, it is preferable to use phenoxy resin from the viewpoint of film formation state, connection reliability, etc. The content of the film-forming resin is preferably 20 to 80 wt%, more preferably 30 to 60 wt%.
[0037] (cationically polymerizable compound) As the cationic polymerizable compound, at least one selected from an epoxy compound and an oxetane compound can be used.
[0038] It is preferable to use an epoxy compound having 5 or less functionalities. Examples of epoxy compounds having 5 or less functionalities include glycidyl ether type epoxy compounds, glycidyl ester type epoxy compounds, alicyclic type epoxy compounds, bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, dicyclopentadiene type epoxy compounds, novolac phenol type epoxy compounds, biphenyl type epoxy compounds, and naphthalene type epoxy compounds, and one of these can be used alone or two or more can be used in combination. A specific example of a commercially available alicyclic epoxy resin is the product name "Celloxide 8000" of Daicel Corporation.
[0039] Examples of the oxetane compound include biphenyl-type oxetane compounds, xylylene-type oxetane compounds, silsesquioxane-type oxetane compounds, ether-type oxetane compounds, phenol novolac-type oxetane compounds, and silicate-type oxetane compounds, and among these, one type may be used alone or two or more types may be used in combination. A specific example of a commercially available biphenyl-type oxetane compound is the product name "OXBP" by UBE Corporation.
[0040] The content of the cationic polymerizable compound is preferably 10 to 70 wt %, more preferably 20 to 50 wt %. If the content of the cationic polymerizable compound is too high, curing shrinkage tends to increase.
[0041] (Aluminum chelate-based latent hardener) Examples of the aluminum chelate-based latent curing agent include an aluminum chelate-based curing agent held in a porous resin obtained by interfacially polymerizing a polyfunctional isocyanate compound and simultaneously radically polymerizing a radically polymerizable compound in the presence of a radical polymerization initiator.
[0042] Specific examples of aluminum chelate-based curing agents include aluminum tris(acetylacetonate), aluminum tris(ethylacetoacetate), aluminum monoacetylacetonate bis(ethylacetoacetate), aluminum monoacetylacetonate bisoleylacetoacetate, ethylacetoacetate aluminum diisopropylate, and alkylacetoacetate aluminum diisopropylate.
[0043] Since the aluminum chelate-based latent curing agent is mainly produced by utilizing an interfacial polymerization method, the shape of the porous resin is spherical, and the size of the pores is preferably 5 to 150 nm from the viewpoints of curability and latency. Also, the average particle size of the aluminum chelate-based latent curing agent is preferably 0.5 to 100 μm from the viewpoints of curability and dispersibility.
[0044] Also, as in Japanese Patent No. 6489494, it is preferable that an aluminum chelate-based curing agent is held in a large number of fine pores present in a porous resin matrix, and the surface is inactivated with an alkoxysilane coupling agent.
[0045] The alkoxysilane coupling agents used in the surface passivation treatment are classified into two types as described below.
[0046] The first type is a type of silane coupling agent that reacts with the active aluminum chelate-based latent curing agent on the surface of the aluminum chelate-based latent curing agent to generate an aluminum chelate-silanol reactant, thereby reducing the electron density of oxygen adjacent to the aluminum atom (in other words, reducing the acidity of hydrogen bonded to oxygen, and further in other words, reducing the polarizability between oxygen and hydrogen), thereby reducing activity. This type of silane coupling agent includes an alkoxysilane coupling agent in which an electron-donating group is bonded to a silicon atom, preferably an alkylalkoxysilane coupling agent having an alkyl group. Specific examples include methyltrimethoxysilane, n-propyltrimethoxysilane, hexyltrimethoxysilane, etc.
[0047] The second type is a silane coupling agent that reduces the activity by covering the surface with epoxy polymer chains generated by reacting the epoxy group in the molecule with the active aluminum chelate-based latent hardener on the surface of the aluminum chelate-based latent hardener. The coupling agent may be an epoxy silane coupling agent, specifically 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (KBM-303, Shin-Etsu Chemical Co., Ltd.), 3-glycidoxypropyltrimethoxysilane (KBM-403, Shin-Etsu Chemical Co., Ltd.), etc.
[0048] The surface inactivation treatment method of the aluminum chelate-based latent curing agent with an alkoxysilane coupling agent includes a method of immersing the aluminum chelate-based latent curing agent in a solution in which the alkoxysilane coupling agent is dissolved in an organic solvent, preferably a non-polar solvent, particularly cyclohexane, at a concentration of preferably 5 to 80% (by mass), for 1 to 20 hours at 25 to 80° C. The solution may be stirred during the immersion.
[0049] The content of the aluminum chelate-based latent curing agent is preferably 1 to 50 wt%, more preferably 3 to 20 wt%. If the content of the aluminum chelate-based latent curing agent is too low, the composition will not cure sufficiently, whereas if the content is too high, the resin properties (e.g., flexibility) of the cured product of the composition will tend to decrease.
[0050] (Silane compounds) The silane compound can cooperate with the aluminum chelate curing agent to initiate cationic polymerization and promote curing. Examples of the silane compound include a highly sterically hindered silanol compound and a silane coupling agent having 1 to 3 lower alkoxy groups in the molecule.
[0051] Specific examples of silanol compounds include tris(tert-pentoxy)silanol, tris(tert-butoxy)silanol, bis(tert-butoxy)(isopropoxy)silanol, etc. Specific examples of silane coupling agents include vinyltris(β-methoxyethoxy)silane, vinyltriethoxysilane, vinyltrimethoxysilane, γ-styryltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, etc.
[0052] The content of the silanol compound is preferably 1 to 50 wt%, more preferably 3 to 20 wt%. If the content of the silanol compound is too low, curing will be insufficient, and if the content is too high, the resin properties after curing will tend to deteriorate.
[0053] (Other additives) The thermal cationic polymerization resin composition preferably contains an inorganic filler. Examples of the inorganic filler that can be used include silica, talc, titanium oxide, calcium carbonate, and magnesium oxide. The inorganic filler may be used alone or in combination of two or more kinds. The content of the inorganic filler is preferably 1 to 50 wt%, and more preferably 3 to 20 wt%. The thermal cationic polymerization resin composition may contain a pigment, an antistatic agent, and the like, as necessary.
[0054] According to such a thermal cationic polymerization resin composition, since an aluminum chelate-based latent curing agent is used, excellent storage stability can be obtained even though it is a one-component type. In addition, since the resin composition contains a highly sterically hindered silanol compound, it can be cationic polymerized at low temperature and fast curing.
[0055] The adhesive film may be a conductive film or anisotropic conductive film using conductive particles. In this case, the conductive particles may be mixed into the resin composition and dispersed three-dimensionally, or may be arranged after the film is formed. When the conductive particles are arranged after the film is formed, they may be arranged two-dimensionally flush with the film surface, and have regularity, as with the latent curing agent. As the conductive particles, known conductive particles used in conductive films can be used. For example, particles of various metals and metal alloys such as nickel, iron, copper, aluminum, tin, lead, chromium, cobalt, silver, and gold, particles of metal oxides, carbon, graphite, glass, ceramics, plastics, etc., coated with metal, and particles of these particles that have been further coated with an insulating thin film or have insulating fine particles attached thereto, etc., which have been subjected to an insulating treatment, may be mentioned. Two or more of these may be mixed. In the case of resin particles coated with metal, the resin particles may be, for example, particles of epoxy resin, phenolic resin, acrylic resin, acrylonitrile-styrene (AS) resin, benzoguanamine resin, divinylbenzene resin, styrene resin, etc.
[0056] The average particle size of the conductive particles is not particularly limited, but the lower limit of the average particle size is preferably 1 μm or more, and the upper limit of the average particle size is preferably 50 μm or less, more preferably 20 μm or less, from the viewpoint of the capture efficiency of the conductive particles in the connection structure. The average particle size can be the particle size at an integrated value of 50% measured by an image particle size distribution meter (for example, FPIA-3000: manufactured by Malvern Instruments).
[0057] [First form] Fig. 5 is a cross-sectional view showing a schematic diagram of an adhesive film of the first embodiment. As shown in Fig. 5, the adhesive film of the first embodiment has a film layer 32 of an adhesive composition in which a latent curing agent 33 is exposed from a first surface 32A or is disposed at least in close proximity to the first surface 32A.
[0058] The lower limit of the thickness T of the film layer 32 may be, for example, the same as the average particle diameter of the latent curing agent 33, and is preferably 1.3 times or more the average particle diameter or 3 μm or more. The upper limit of the thickness T of the film layer 32 may be, for example, 40 μm or less or 12 times or less the average particle diameter. The film thickness can be measured using a known micrometer or digital thickness gauge. The film thickness can be calculated as an average value by measuring, for example, 10 or more points.
[0059] The lower limit of the average particle size of the latent curing agent 33 is preferably 2 μm or more, and the upper limit of the particle size is, for example, preferably 50 μm or less, and more preferably 20 μm or less. The average particle size can be the particle size at an integrated value of 50% measured by an image particle size distribution meter (for example, FPIA-3000: manufactured by Malvern Instruments).
[0060] Fig. 6 is a cross-sectional view showing a schematic diagram of a modified example of the adhesive film of the first embodiment. As shown in Fig. 6, the adhesive film may have the latent curing agent 34 arranged in the film layer 32 in the form of lumps. In the case of lumps, it is preferable that the size of the lumps satisfies the upper and lower limits described above. The average particle size of the lumps of latent curing agent 33 can be obtained by observation with an electron microscope such as SEM. In this case, it is preferable that the number of samples for measuring the particle size is 200 or more.
[0061] The embedding depth T of the latent hardener 33 in the film layer 32 A The lower limit of the embedding depth T is preferably 0.8 times or more, more preferably 1.0 times or more, of the average particle diameter of the latent hardener 33. AThe upper limit of is preferably 1.5 times or less, more preferably 1.2 times or less, of the average particle size of the latent curing agent 33. That is, the latent curing agent 33 may be exposed on the surface of the film layer 32 or may be completely embedded therein. The embedding depth of the latent curing agent in the film layer can be determined by observation with an electron microscope such as SEM.
[0062] The latent curing agent 33 may be arranged randomly or with regularity in the plan view of the first surface 32A. Among these, the latent curing agent 33 is preferably arranged in a regular arrangement such as a lattice or a staggered arrangement. Examples of the lattice include an oblique lattice, a hexagonal lattice, a square lattice, a rectangular lattice, and a parallelepiped lattice. This makes the particle surface density of the latent curing agent 33 arranged on the surface uniform, and the adhesive strength (die shear strength, peel strength) can be further improved. The latent curing agent may be arranged alone or in the form of aggregates. Even if the latent curing agent is aggregated, it is preferable that the aggregated lumps are arranged with regularity as described above.
[0063] [Second Form] Fig. 7 is a cross-sectional view showing a schematic diagram of an adhesive film of the second embodiment. As shown in Fig. 7, the adhesive film of the second embodiment has a film layer 42 of an adhesive composition in which a latent curing agent 43A is exposed from a first surface 42A or disposed adjacent to the first surface 42A, and a latent curing agent 43B is exposed from a second surface 42B or disposed adjacent to the second surface 42B.
[0064] The lower limit of the thickness of the film layer 42 may be, for example, the same as the average particle diameter of the latent curing agents 43A and 43B, and may preferably be 1.3 times or more the average particle diameter or 3 μm or more. When the thickness of the film layer 42 is less than twice the sum of the average particle diameter of the latent curing agent 43A and the average particle diameter of the latent curing agent 43B, it is desirable to arrange the latent curing agent 43A on the first surface 42A and the latent curing agent 43B on the second surface 42B so that they do not overlap in a plan view. In addition, the thickness of the film layer 42 may be, for example, the same as the sum of the average particle diameter of the latent curing agent 43A and the average particle diameter of the latent curing agent 43B, and may preferably be 1.3 times or more the sum of the average particle diameters. In addition, the upper limit of the thickness of the film layer 42 may be, for example, 40 μm or less, or, for example, 12 times or less the sum of the average particle diameter of the latent curing agent 43A and the average particle diameter of the latent curing agent 43B. The embedding depth T of the latent curing agent 43A in the film layer 42 A and the embedding depth T of the latent hardener 43A B Since this is the same as in the first embodiment, the explanation will be omitted.
[0065] In addition, when the latent curing agents 43A and 43B are disposed on both sides of the film layer 42, when the film layers 42 are laminated, or when the film layer 32 having the latent curing agent 33 disposed on one side is laminated, the distance D between adjacent latent curing agents in the film thickness direction is preferably 5 times or less, more preferably 3 times or less, and even more preferably 2 times or less, of the average particle size of the latent curing agent. This reduces the bias of the latent curing agent in the film thickness direction, so that excellent adhesion can be obtained. The distance between adjacent latent curing agents in the film thickness direction can be obtained by observation with an electron microscope such as SEM as the distance between the average position of the center of the latent curing agent disposed on one side and the average position of the center of the latent curing agent disposed on the other side.
[0066] The latent curing agents 43A and 43B may be arranged randomly or regularly in a plan view of the first surface 42A or the second surface 42B, as in the first embodiment. Among these, the latent curing agents 43A and 43B are preferably arranged in a regular pattern such as a lattice pattern or a staggered pattern. This makes the particle surface density of the latent curing agents 43A and 43B arranged on both surfaces uniform, and can further improve the adhesive strength (die shear strength and peel strength).
[0067] [Third Form] FIG. 8 is a cross-sectional view showing a schematic diagram of an adhesive film of the third embodiment. As shown in FIG. 8, the adhesive film of the third embodiment has a film layer 52 of an adhesive composition in which a latent curing agent 53A is exposed from a first surface 52A or is arranged adjacent to the first surface 52A, and a conductive particle 54 is exposed from a second surface 52B or is arranged adjacent to the second surface 52B. The adhesive film of the third embodiment also has a film layer 42 of an adhesive composition in which a latent curing agent 43A is exposed from a first surface 42A or is arranged adjacent to the first surface 42A, and a latent curing agent 43B is exposed from a second surface 42B or is arranged adjacent to the second surface 42B. That is, the adhesive film of the third embodiment is obtained by laminating a film layer 42 on a first surface 52A of the film layer 52. The film layer 42 is the same as that of the second embodiment, and therefore will not be described.
[0068] The lower limit of the thickness of the film layer 52 may be, for example, the same as the average particle size of the latent curing agent 53 and the conductive particles 54, and can be preferably 1.3 times or more the average particle size or 3 μm or more. When the thickness of the film layer 52 is less than twice the sum of the average particle size of the latent curing agent 53 and the average particle size of the conductive particles 54, it is desirable to arrange the latent curing agent 53 on the first surface 52A and the conductive particles 54 on the second surface 52B so that they do not overlap in a plan view.
[0069] The latent curing agent 53 arranged on the first surface 52A preferably has regularity, similar to the first form, and is preferably arranged in a regular grid, staggered pattern, etc. This makes the particle surface density of the latent curing agent 53 arranged on the surface uniform, and can further improve the adhesive strength (die shear strength, peel strength).
[0070] The conductive particles 53 may be dispersed in the film layer 52, and preferably have regularity, and are preferably arranged in a regular pattern such as a lattice pattern or a staggered pattern in a plan view. Examples of lattice patterns include an oblique lattice, a hexagonal lattice, a square lattice, a rectangular lattice, and a parallelepiped lattice. This makes the particle surface density of the conductive particles 53 arranged on the surface uniform, improving the connection reliability.
[0071] <3. Manufacturing method of structure and structure> The manufacturing method of the connection body according to the present embodiment bonds the first component and the second component via the above-mentioned adhesive film, and the connection body according to the present embodiment is formed by bonding the first component and the second component via the above-mentioned adhesive film. The adhesive film may be a conductive film or an anisotropic conductive film, and the manufacturing method of the connection structure may connect the terminal of the first electronic component and the terminal of the second electronic component via the conductive film or the anisotropic conductive film, or the connection structure may be a connection structure in which the terminal of the first electronic component and the terminal of the second electronic component are connected via the conductive film or the anisotropic conductive film.
[0072] The first electronic component and the second electronic component are not particularly limited and can be appropriately selected according to the purpose. Examples of the first electronic component include plastic substrates, glass substrates, printed wiring boards (PWBs), etc., for use in LCD (Liquid Crystal Display) panels and organic electroluminescence (OLED) panels. Examples of the second electronic component include flexible printed circuits (FPCs) such as integrated circuits (ICs) and chip-on-film (COFs), and tape carrier package (TCP) substrates.
[0073] When connecting, a pressure bonding tool heated to a predetermined temperature is used to apply a predetermined pressure and time from above the second electronic component, connecting the terminals of the first electronic component and the terminals of the second electronic component. In addition, when the adhesive film is a conductive film or anisotropic conductive film, the conductive particles are sandwiched and crushed between the terminals of the first electronic component and the terminals of the second electronic component, and the binder hardens in this state.
[0074] The predetermined pressure during the heat and pressure application is preferably 1 MPa or more and 150 MPa or less from the viewpoint of preventing wiring cracks in electronic components. The predetermined temperature is preferably 80° C. or more and 230° C. or less. When a photoreaction initiator is blended, light irradiation such as UV may be used in combination.
[0075] Also, the thermocompression bonding may be performed with a buffer material interposed between the bonding tool and the second electronic component. By interposing the buffer material, it is possible to reduce the variation in pressing force and prevent the bonding tool from becoming dirty. The buffer material is made of a sheet-like elastic material or plastic body, such as polytetrafluoroethylene (Teflon (trademark)) or silicone rubber.
[0076] According to the manufacturing method of such a structure, an adhesive film having a latent hardener disposed on the surface of the foam layer is used, so that the hardener reaction starts simultaneously, and excellent adhesive strength (die shear strength, peel strength) can be obtained.
[0077] In addition, the present technology is not limited to the above-mentioned embodiment, but can also be applied to a material that undergoes undesirable chemical or physical changes in the presence of a solvent in a method of mixing, dissolving, or dispersing a material and a solvent for coating and drying in the process of producing a film. For example, a material having solubility or coagulation properties can be disposed on the film surface.
[0078] In addition, the method is not limited to the use of solvents, and can also be applied to materials that change when mixed or stirred before being made into a film. It is also possible to transfer materials with different reactivity to both sides of the same film, control the properties, or transfer materials that react with each other. EXAMPLES
[0079] <4. Examples> In this example, an anisotropic conductive film containing conductive particles was produced as a form of an adhesive film. A connection structure was produced using the anisotropic conductive film, and the conduction resistance, adhesive strength, and storage stability were evaluated.
[0080] [Preparation of anisotropic conductive film] An anisotropic conductive film was produced using the following materials. The size of the film was 20 cm x 30 cm. Phenoxy resin: YP50, Nippon Steel Chemical & Material Co., Ltd. Epoxy resin: YD-019, Nippon Steel Chemical & Material Co., Ltd. Silica filler: Aerosil 805, Nippon Aerosil Co., Ltd. Alicyclic epoxy resin: Celloxide 8000, Daicel Corporation Oxetane compound: OXBP, UBE Corporation Silane coupling agent: KBM-403, Shin-Etsu Chemical Co., Ltd. Thermal cationic curing agent: SI-60L, Sanshin Chemical Industry Co., Ltd. Silanol compound: Tris(tert-pentoxy)silanol (TPS) Conductive particles (resin core metal coated conductive particles): AUL704, Sekisui Chemical Co., Ltd., 4μmφ
[0081] (Preparation of aluminum chelate-based latent hardener) 800 parts by mass of distilled water, 0.05 parts by mass of a surfactant (Newrex RT, NOF Corporation), and 4 parts by mass of polyvinyl alcohol (PVA-205, Kuraray Co., Ltd.) as a dispersant were placed in a 3-liter interfacial polymerization vessel equipped with a thermometer and mixed uniformly to prepare an aqueous phase.
[0082] To this aqueous phase, 350 parts by mass of a 24% isopropanol solution of aluminum monoacetylacetonate bis(ethylacetoacetate) (Aluminum Chelate D, Kawaken Fine Chemicals Co., Ltd.), 49 parts by mass of a multifunctional isocyanate compound, a trimethylolpropane (1 mole) adduct of methylenediphenyl-4,4'-diisocyanate (3 moles) (D-109, Mitsui Chemicals, Inc.), 21 parts by mass of divinylbenzene (Merck Co., Ltd.) as a radical polymerizable compound, and 0.21 parts by mass of a radical polymerization initiator (Perloil L, NOF Corp.) (corresponding to 1% by mass of the radical polymerizable compound) dissolved in 70 parts by mass of ethyl acetate were added, and the mixture was emulsified and mixed with a homogenizer (10,000 rpm / 5 min: T-50, IKA Japan Co., Ltd.), followed by interfacial polymerization and radical polymerization at 80°C for 6 hours. After the reaction was completed, the polymerization reaction liquid was allowed to cool to room temperature, and the polymer particles were separated by filtration and naturally dried to obtain spherical particles of an aluminum chelate-based latent curing agent that had not been subjected to a surface passivation treatment.
[0083] This aluminum chelate-based latent curing agent was added to an impregnation liquid consisting of 40 parts by mass of a 24% isopropanol solution of aluminum monoacetylacetonate bis(ethylacetoacetate) (Aluminum Chelate D, Kawaken Fine Chemical Co., Ltd.) and 60 parts by mass of ethanol, and after stirring at 30°C for 6 hours, the particulate curing agent was filtered off and allowed to dry naturally, thereby obtaining a high-concentration type spherical aluminum chelate-based latent curing agent that had not been subjected to surface passivation treatment.
[0084] Then, 3 parts by mass of n-propyltrimethoxysilane (KBM-303, Shin-Etsu Chemical Co., Ltd.) was dissolved in 27 parts by mass of cyclohexane to prepare a surface passivation treatment liquid, and 3 parts by mass of an aluminum chelate-based latent curing agent that had not been subjected to surface passivation treatment was added to 30 parts by mass of this treatment liquid, and the mixture was stirred at 200 rpm for 20 hours at 30° C. to perform surface passivation treatment of the aluminum chelate-based latent curing agent. After the treatment reaction was completed, the polymerized particles were filtered out from the treatment liquid and naturally dried to obtain a spherical aluminum chelate-based latent curing agent that had been subjected to surface passivation treatment of a high concentration type.
[0085] Moreover, the average particle size of the aluminum chelate-based latent curing agent was measured using an automatic flow particle imaging analyzer (FPIA-3000 (Malvern Instruments)) and found to be 3 μm.
[0086] (Preparation of transfer substrate) Predetermined density (12000 pieces / mm 2 , 24000 pieces / mm 2 , 36000 pieces / mm 2 A mold with a square lattice arrangement and convex portions of 12,000 pieces / mm was fabricated. Transparent resin pellets were poured in a molten state into the mold and cooled and solidified to produce the desired density of 12,000 pieces / mm. 2 , 24000 pieces / mm 2 , 36000 pieces / mm 2 A transfer substrate having a square lattice arrangement of recesses of 100 nm was fabricated.
[0087] [Fabrication of connection structure] The following evaluation ICs and glass substrates were prepared. (Conduction characteristic evaluation IC) External size 1.8×20.0mm Thickness 0.5mm Bump specifications: Size 30 x 85 μm, distance between bumps 50 μm, bump height 9 μm (Glass substrate) Glass material: Corning 1737F External size 30×50mm Thickness 0.5mm Electrode ITO wiring
[0088] The anisotropic conductive film of each Example and Comparative Example was cut to an area sufficient for connection, sandwiched between an IC for evaluating the conductive characteristics and a glass substrate, and pressed under compression conditions of a temperature of 130°C, a pressure of 70 MPa, and a time of 5 sec or a temperature of 160°C, a pressure of 70 MPa, and a time of 5 sec to produce a connection structure.
[0089] [Evaluation of conduction resistance] For the connection structures produced under crimping conditions at a temperature of 130° C. or 160° C., the resistance value (Ω) was measured using a digital multimeter (34401A, manufactured by Agilent Technologies, Inc.) by a four-terminal method when a current of 1 mA was passed through the connection structures. The conductive resistance was evaluated for the connection structures (N=10) of the examples and comparative examples according to the following criteria, with the lowest evaluation being the evaluation of the example or comparative example. A: Maximum resistance is less than 2Ω B: Maximum resistance is between 2Ω and 4Ω C: Maximum resistance is over 4Ω
[0090] [Evaluation of die shear strength] The die shear strength of the evaluation IC was measured using a die shear tester (4000 series, Nordson Advanced Technology Co., Ltd.) at a tool speed of 0.2 mm / sec for the connection structures produced under pressure bonding conditions at a temperature of 130° C. or 160° C. The die shear strength was evaluated for the connection structures (N=10) of the examples or comparative examples according to the following criteria, with the lowest evaluation being the evaluation of the example or comparative example. AA: Die shear strength over 900N A: Die shear strength is between 600N and 900N B: Die shear strength is 300N or more and 600N or less C: Die shear strength is less than 300N
[0091] [Evaluation of storage stability] The anisotropic conductive film was aged under environmental conditions of temperature 40°C-time 8h. Using the aged anisotropic conductive film, a connection structure was produced under pressure bonding conditions of temperature 130°C-pressure 70MPa-time 5sec, similar to the above-mentioned method for producing a connection structure. Then, the die shear strength of the connection structure connected using the aged anisotropic conductive film was measured in the same manner as the above-mentioned evaluation of die shear strength. The storage stability was evaluated by the following criteria for the connection structures (N=10) of the examples or comparative examples, relative to the die shear strength of the connection structure connected using the anisotropic conductive film that was not aged, and the lowest evaluation was the evaluation of the examples or comparative examples. AA: Less than 10% decrease in die shear strength A: Decrease in die shear strength is between 10% and 30% B: Decrease in die shear strength is 30% or more and 50% or less C: Die shear strength reduction of more than 50%
[0092] <Example 1> In Example 1, a film layer of a curing agent-free adhesive composition not containing a curing agent was formed, and a transfer substrate on which a latent curing agent was arranged was used to transfer the latent curing agent to the film layer, to produce a conductive particle-containing layer A1. Similarly, a film layer of a curing agent-free adhesive composition not containing a curing agent was formed, and a transfer substrate on which a latent curing agent was arranged was used to transfer the latent curing agent to the film layer, to produce a conductive particle-free layer N1. Then, a conductive particle-free layer N1 was laminated on the transfer surface of the aluminum chelate-based latent curing agent of the conductive particle-containing layer A1, to produce a two-layer anisotropic conductive film.
[0093] (Conductive particle containing layer A1) The materials shown in Table 1 were mixed in the presence of a solvent, propylene glycol monomethyl ether acetate (PMA), to obtain a binder composition. This binder composition was applied onto a PET film using a bar coater and dried in an oven at 80°C for 5 minutes to form a binder layer with a thickness of 4 μm on the PET film.
[0094] Count density: 24000 pieces / mm 2 The conductive particles were filled in the recesses of the transfer substrate, one side of the binder layer was placed on top of the conductive particles, and pressure was applied (conditions: temperature 40-50°C, pressure 0.5 MPa) to attach the conductive particles to the surface of the binder layer. The binder layer was then peeled off from the transfer substrate, and the conductive particles on the binder layer were pressed (conditions: temperature 40-50°C, pressure 0.5 MPa) to push them into the binder layer, thereby disposing the conductive particles on one side of the binder layer.
[0095] Using a transfer substrate in which recesses were formed at a predetermined density, the recesses were filled with aluminum chelate-based latent curing agent so that the amount of aluminum chelate-based latent curing agent in the film layer was 4 wt%, and the aluminum chelate-based latent curing agent in areas other than the recesses was removed with a squeegee. One side of the binder layer was placed on the transfer substrate in which the recesses were filled with the aluminum chelate-based latent curing agent, and the aluminum chelate-based latent curing agent was attached to the surface of the binder layer by applying pressure (conditions: temperature 40 to 50°C, pressure 0.5 MPa). Then, the binder layer was peeled off from the transfer substrate, and the aluminum chelate-based latent curing agent on the binder layer was pressed (conditions: temperature 40 to 50°C, pressure 0.5 MPa) and pressed into the binder layer, so that the aluminum chelate-based latent curing agent was disposed on the other side of the binder layer, and a conductive particle-containing layer A1 was produced.
[0096] (Conductive particle-free layer N1) The materials shown in Table 1 were mixed in the presence of a solvent, propylene glycol monomethyl ether acetate (PMA), to obtain a binder composition. This binder composition was applied onto a PET film using a bar coater and dried in an oven at 80°C for 5 minutes to form a binder layer with a thickness of 8 μm on the PET film.
[0097] Using a transfer substrate in which recesses were formed at a predetermined density, the recesses were filled with an aluminum chelate-based latent curing agent so that the amount of the aluminum chelate-based latent curing agent in the film layer was 4 wt%, and the aluminum chelate-based latent curing agent in areas other than the recesses was removed with a squeegee. One side of the binder layer was placed on the transfer substrate in which the recesses were filled with the aluminum chelate-based latent curing agent, and the aluminum chelate-based latent curing agent was attached to the surface of the binder layer by applying pressure (conditions: temperature 40 to 50°C, pressure 0.5 MPa). Then, the binder layer was peeled off from the transfer substrate, and the aluminum chelate-based latent curing agent on the binder layer was pressed (conditions: temperature 40 to 50°C, pressure 0.5 MPa) and pushed into the binder layer, thereby disposing the aluminum chelate-based latent curing agent on one side of the binder layer. Similarly, the aluminum chelate-based latent curing agent was disposed on the other side of the binder layer to produce a conductive particle-free layer N1.
[0098] Table 1 shows the evaluation results of the conduction resistance, die shear strength, and storage stability of Example 1. In Example 1, since the aluminum chelate-based latent curing agent is disposed after film formation, the influence of the solvent is suppressed, and excellent conduction resistance, die shear strength, and storage stability can be obtained. In addition, when the cross section of the two-layered anisotropic conductive film produced in Example 1 was observed with an electron microscope, the distance in the film thickness direction between adjacent latent curing agents was a maximum of about 5 μm in the conductive particle-free layer N1.
[0099] <Comparative Example 1> In Comparative Example 1, a film layer of a curing agent-free adhesive composition not containing a curing agent was formed, and a latent curing agent was sprinkled on the surface of the film layer to produce a conductive particle-containing layer A2. Similarly, a film layer of a curing agent-free adhesive composition not containing a curing agent was formed, and a latent curing agent was sprinkled on the surface of the film layer to produce a conductive particle-free layer N2. Then, a conductive particle-free layer N2 was laminated on the surface of the conductive particle-containing layer A2 on which the aluminum chelate-based latent curing agent was sprinkled, to produce a two-layer anisotropic conductive film.
[0100] (Conductive particle containing layer A2) The materials shown in Table 1 were mixed in the presence of a solvent, propylene glycol monomethyl ether acetate (PMA), to obtain a binder composition. This binder composition was applied onto a PET film using a bar coater and dried in an oven at 80°C for 5 minutes to form a binder layer with a thickness of 4 μm on the PET film.
[0101] Count density: 24000 pieces / mm 2 The conductive particles were filled in the recesses of the transfer substrate, one side of the binder layer was placed on top of the conductive particles, and pressure was applied (conditions: temperature 40-50°C, pressure 0.5 MPa) to attach the conductive particles to the surface of the binder layer. The binder layer was then peeled off from the transfer substrate, and the conductive particles on the binder layer were pressed (conditions: temperature 40-50°C, pressure 0.5 MPa) to push them into the binder layer, thereby disposing the conductive particles on one side of the binder layer.
[0102] The aluminum chelate-based latent curing agent was sprinkled on the other side of the binder layer so that the amount of the aluminum chelate-based latent curing agent was 4 wt%, and the aluminum chelate-based latent curing agent was attached to the surface of the binder layer. Then, the aluminum chelate-based latent curing agent on the binder layer was pressed (conditions: temperature 40 to 50°C, pressure 0.5 MPa) and pressed into the binder layer, so that the aluminum chelate-based latent curing agent was disposed on the other side of the binder layer, and the conductive particle-containing layer A2 was produced.
[0103] (Conductive particle-free layer N2) The materials shown in Table 1 were mixed in the presence of a solvent, propylene glycol monomethyl ether acetate (PMA), to obtain a binder composition. This binder composition was applied onto a PET film using a bar coater and dried in an oven at 80°C for 5 minutes to form a binder layer with a thickness of 8 μm on the PET film.
[0104] The aluminum chelate-based latent curing agent was sprinkled on one side of the binder layer so that the amount of the aluminum chelate-based latent curing agent in the film layer was 4 wt%, and the aluminum chelate-based latent curing agent was attached to the surface of the binder layer. Then, the aluminum chelate-based latent curing agent on the binder layer was pressed (conditions: temperature 40 to 50°C, pressure 0.5 MPa) and pressed into the binder layer, so that the aluminum chelate-based latent curing agent was disposed on one side of the binder layer. Similarly, the aluminum chelate-based latent curing agent was sprinkled on the other side of the binder layer, and the aluminum chelate-based latent curing agent was disposed on the other side of the binder layer, to prepare a conductive particle-free layer N2.
[0105] Table 1 shows the evaluation results of the conduction resistance, die shear strength, and storage stability of Comparative Example 1. In Comparative Example 1, since the aluminum chelate-based latent curing agent was sprinkled and arranged, the aluminum chelate-based latent curing agent was partially concentrated and there were places where the curing was insufficient, and excellent conduction resistance, die shear strength, and storage stability could not be obtained. In Comparative Example 1, there were also connection structures that obtained sufficient performance, and the conduction resistance was the best at both low and high temperatures and was rated A, the die shear strength was the best at both low and high temperatures and was rated AA, and the storage stability was also the best and was rated AA. This is presumably because the latent curing agent was sprinkled by hand, and the performance of the adhesive film was reduced in some places, and the performance of the adhesive film was not stable.
[0106] <Comparative Example 2> In Comparative Example 2, an adhesive composition was prepared by mixing an aluminum chelate-based latent curing agent and a silanol compound, as shown in Table 1, and an attempt was made to prepare a conductive particle-containing layer A3 and a conductive particle-free layer N3. However, in Comparative Example 2, in the preparation of the conductive particle-containing layer A3 and the conductive particle-free layer N3, the aluminum chelate-based latent curing agent reacted with the solvent during mixing, generating heat and curing, and it was not possible to form a film.
[0107] [Table 1]
[0108] <Example 2> In Example 2, a conductive particle-containing layer A4 was prepared in the same manner as the conductive particle-containing layer A1, except that a transfer substrate was used in which recesses were formed at a predetermined number density so that the amount of the aluminum chelate-based latent curing agent in the film layer was 8 wt%. A conductive particle-free layer N4 was prepared in the same manner as the conductive particle-free layer N1, except that a transfer substrate was used in which recesses were formed at a predetermined number density so that the amount of the aluminum chelate-based latent curing agent in the film layer was 8 wt%. Then, a conductive particle-free layer N4 was laminated on the transfer surface of the aluminum chelate-based latent curing agent of the conductive particle-containing layer A4, to prepare a two-layer anisotropic conductive film.
[0109] Table 2 shows the evaluation results of the conduction resistance, die shear strength, and storage stability of Example 2. In Example 2, an aluminum chelate-based latent curing agent is disposed after film formation, so that the influence of the solvent is suppressed and excellent conduction resistance, die shear strength, and storage stability can be obtained. In addition, the die shear strength at high temperatures was superior to that of Example 1.
[0110] <Example 3> In Example 3, a conductive particle-containing layer A5 was prepared in the same manner as the conductive particle-containing layer A1, except that a transfer substrate was used in which recesses were formed at a predetermined number density so that the amount of aluminum chelate-based latent curing agent in the film layer was 12 wt%. A conductive particle-free layer N5 was prepared in the same manner as the conductive particle-free layer N1, except that a transfer substrate was used in which recesses were formed at a predetermined number density so that the amount of aluminum chelate-based latent curing agent in the film layer was 12 wt%. Then, a conductive particle-free layer N5 was laminated on the transfer surface of the aluminum chelate-based latent curing agent of the conductive particle-containing layer A5, to prepare a two-layer anisotropic conductive film.
[0111] Table 2 shows the evaluation results of the conduction resistance, die shear strength, and storage stability of Example 3. In Example 3, an aluminum chelate-based latent curing agent is disposed after film formation, so that the influence of the solvent is suppressed and excellent conduction resistance, die shear strength, and storage stability can be obtained. In addition, the die shear strength at high and low temperatures was superior to that of Example 1.
[0112] <Example 4> In Example 4, the materials shown in Table 2 were mixed in the presence of a solvent of propylene glycol monomethyl ether acetate (PMA), and the number density was adjusted to 24,000 particles / mm 2 A predetermined amount of conductive particles was mixed so as to obtain a binder composition. This binder composition was applied onto a PET film with a bar coater and dried in an oven at a temperature of 80°C for 5 minutes to form a binder layer with a thickness of 4 μm on the PET film. Then, a conductive particle-containing layer A6 was produced in the same manner as the conductive particle-containing layer A1, except that a transfer substrate was used in which recesses were formed at a predetermined number density so that the amount of the aluminum chelate-based latent curing agent in the film layer was 8 wt%.
[0113] In addition, a conductive particle-free layer N6 was prepared in the same manner as the conductive particle-free layer N1, except that a transfer substrate was used in which recesses were formed at a predetermined number density so that the blending amount of the aluminum chelate-based latent curing agent in the film layer was 8 wt%. Then, the conductive particle-free layer N6 was laminated on the transfer surface of the aluminum chelate-based latent curing agent of the conductive particle-containing layer A6, to prepare a two-layer anisotropic conductive film.
[0114] Table 2 shows the evaluation results of the conduction resistance, die shear strength, and storage stability of Example 4. In Example 4, an aluminum chelate-based latent curing agent is disposed after film formation, so that the influence of the solvent is suppressed and excellent conduction resistance, die shear strength, and storage stability can be obtained. In addition, the die shear strength at high temperatures was superior to that of Example 1.
[0115] <Comparative Example 3> In Comparative Example 3, a conductive particle-containing layer A7 and a conductive particle-free layer N7 were prepared using a thermal cationic polymerization initiator instead of a silanol compound and an aluminum chelate-based latent curing agent. The materials shown in Table 2 were mixed in the presence of a solvent such as propylene glycol monomethyl ether acetate (PMA) to obtain a binder composition. This binder composition was applied to a PET film using a bar coater and dried in an oven at a temperature of 80°C for 5 minutes to form a binder layer having a thickness of 4 μm on the PET film.
[0116] Count density: 24000 pieces / mm 2 The conductive particles were filled in the recesses of the transfer substrate, one side of the binder layer was placed on top of the conductive particles, and pressure was applied (conditions: temperature 40-50°C, pressure 0.5 MPa) to attach the conductive particles to the surface of the binder layer. The binder layer was then peeled off from the transfer substrate, and the conductive particles on the binder layer were pressed (conditions: temperature 40-50°C, pressure 0.5 MPa) to push them into the binder layer, disposing the conductive particles on one side of the binder layer to produce a conductive particle-containing layer A7.
[0117] In addition, the materials shown in Table 1 were mixed in the presence of a solvent, propylene glycol monomethyl ether acetate (PMA), to obtain a binder composition. This binder composition was applied to a PET film with a bar coater and dried in an oven at a temperature of 80°C for 5 minutes to form a binder layer with a thickness of 8 μm on the PET film, thereby producing a conductive particle-free layer N7. Then, the conductive particle-containing layer A7 and the conductive particle-free layer N7 were laminated to produce a two-layer anisotropic conductive film.
[0118] Table 2 shows the evaluation results of the conduction resistance, die shear strength, and storage stability of Comparative Example 3. In Comparative Example 3, since a thermocationic curing agent with high solvent resistance was used, an anisotropic conductive film could be produced, but the die shear strength in low-temperature compression bonding was small and the storage stability was also low. This is thought to be due to the effect of the solvent on the curing agent during film formation.
[0119] [Table 2] [Explanation of symbols]
[0120] 11 base film, 12 film layer, 12A first surface, 13 latent hardener, 20 transfer substrate, 32 film layer, 32A first surface, 32B second surface, 33 latent hardener, 34 latent hardener, 42 film layer, 42A first surface, 42B second surface, 43A latent hardener, 43B latent hardener, 52 film layer, 52A first surface, 52B second surface, 53 latent hardener, 53 conductive particles
Claims
1. forming a film layer of a non-curing agent-containing adhesive composition that does not contain a curing agent; a disposing step of transferring the latent curing agent from a transfer substrate on which the latent curing agent is disposed to the film layer, and disposing the latent curing agent so as to be exposed from at least one surface of the film layer or to be adjacent to at least one surface of the film layer; A method for producing an adhesive film having the above structure.
2. The method for producing an adhesive film according to claim 1 , wherein the latent curing agent is disposed in the film layer in the form of a mass.
3. 3. The method for producing an adhesive film according to claim 1, wherein the latent curing agent is in a microcapsule type.
4. the curing agent-free adhesive composition comprises a film-forming resin, a cationically polymerizable compound, and a silane-based compound; 3. The method for producing an adhesive film according to claim 1, wherein the latent curing agent is an aluminum chelate-based latent curing agent.
5. 3. The method for producing an adhesive film according to claim 1, further comprising a conductive particle arranging step of arranging conductive particles in the film layer.
6. The method for producing an adhesive film according to claim 1 or 2, wherein in the forming step, conductive particles are blended with the curing agent-free adhesive composition, and a film layer containing the conductive particles is formed.
7. A film layer of an adhesive composition having a latent curing agent exposed from at least one surface or disposed adjacent to at least one surface, The average particle size of the latent curing agent is 2 μm or more and 50 μm or less, The thickness of the film layer is from 3 μm to 40 μm.
8. a latent curing agent is exposed from at least one surface or disposed adjacent to at least one surface, the film layer containing conductive particles; The average particle size of the latent curing agent is 2 μm or more and 50 μm or less, The conductive film, wherein the thickness of the film layer is 3 μm or more and 40 μm or less.
9. a latent curing agent is exposed from at least one surface or disposed adjacent to at least one surface, the film layer containing conductive particles; The average particle size of the latent curing agent is 2 μm or more and 50 μm or less, The thickness of the film layer is 3 μm or more and 40 μm or less.
10. A method for manufacturing a structure in which a first part and a second part are bonded together via the adhesive film according to claim 7.
11. A method for manufacturing a connection structure in which a terminal of a first component and a terminal of a second component are connected via the adhesive film described in claim 7, the conductive film described in claim 8, or the anisotropic conductive film described in claim 9.
12. A structure in which a first part and a second part are bonded together via the adhesive film according to claim 7.
13. A connection structure in which a terminal of a first electronic component and a terminal of a second electronic component are connected via the adhesive film described in claim 7, the conductive film described in claim 8, or the anisotropic conductive film described in claim 9.
Citation Information
Patent Citations
Aluminum chelate-based latent curing agent, method for producing the same, and thermosetting epoxy resin composition
JP2016056274A
